2017
DOI: 10.5860/rusq.56.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Why do Students Seek Help in an Age of DIY? Using a Qualitative Approach to Look Beyond Statistics

Abstract: National statistics indicate that academic libraries are experiencing declines in reference transactions, but the references services in some libraries continue to thrive. While many studies explore reasons that students do not seek assistance from librarians, there is limited research explaining why students do ask for help. The authors conducted a study to answer two questions: (1) How do undergraduate students look for information? (2) What prompted the students to seek out help from a librarian? To answer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Interviews were audio-recorded and transcribed followed by an applied thematic analysis technique (Guest et al, 2012;Vinyard et al, 2017). Two researchers independently engaged in an iterative process of reading the transcripts and generating codes, then met to discuss and come to agreement on the coding.…”
Section: Design and Methodology Approachmentioning
confidence: 99%
“…Interviews were audio-recorded and transcribed followed by an applied thematic analysis technique (Guest et al, 2012;Vinyard et al, 2017). Two researchers independently engaged in an iterative process of reading the transcripts and generating codes, then met to discuss and come to agreement on the coding.…”
Section: Design and Methodology Approachmentioning
confidence: 99%
“…The authors found that many students thought that the reference desk consultations saved them time, while others claimed that they had no time for the consultations. Vinyard, Mullally, and Colvin (2017) argued that "students' perceptions of their research skills can influence their decision to seek help" (261). In their study interviewing ten undergraduates at Pepperdine University, the authors discovered a "do-it-yourself" attitude, despite some students more confident than others in their research skill abilities (265).…”
Section: Literature Reviewmentioning
confidence: 99%
“…12 Vinyard, Mullally, and Colvin explored how students search for information, as well as what prompted students to seek help from a librarian. 13 Through one-on-one interviews, the authors determined that students preferred searching for information independently, and would seek assistance only when frustrated by the amount of time it took to perform research. Once connected with a librarian for assistance, all of the study participants stated that they found the librarians to be helpful and would ask for research assistance in the future.…”
Section: Literature Reviewmentioning
confidence: 99%